Personally oriented education: the variety of paradigms - Fasolia, A. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The existing paradigms of personally oriented education are characterized in the paper. There had been described the essence, given features, principles, functions of culturological paradigm, its correspondence to contemporary requirements.